Telerehabilitation in heart failure patients: The evidence and the pitfalls - Piotrowicz, Ewa; Piepoli, Massimo F.; Jaarsma, Tiny; Lambrinou, Ekaterini; Coats, Andrew J.S.; Schmid, Jean-Paul; Corrà, Ugo; Agostoni, Piergiuseppe; Dickstein, Kenneth; Seferović, Petar M.; Adamopoulos, Stamatis; Ponikowski, Piotr P. (My University, 2016)
Accessibility to the available traditional forms of cardiac rehabilitation programs in heart failure patients is not adequate and adherence to the programs remains unsatisfactory. The home-based telerehabilitation model has been proposed as a promising new option to improve this situation. This paper's aims are to discuss the tools available for telemonitoring, and describing their characteristics, applicability, and effectiveness in providing optimal long term management for heart failure patients who are unable to attend traditional cardiac rehabilitation programs. The critical issues of psychological support and adherence to the telerehabilitation programs are outlined. The advantages and limitations of this long term management modality are presented and compared with alternatives. Finally, the importance of further research, multicenter studies of telerehabilitation for heart failure patients and the technological development needs are outlined, in particular interactive remotely controlled intelligent telemedicine systems with increased inter-device compatibility.
Keywords: Exercise training; Heart failure; Telerehabilitation